Bangladesh : Fiscal Costs of Non-Financial Public Corporations - Kojo, Naoko C. (World Bank, Washington, DC, 2015)
The overall fiscal position of Bangladesh looks sustainable, but there are concerns that the country may be trapped in a low revenue-low capital spending equilibrium, which is holding back Bangladesh’s growth potential. Eliminating wasteful spending and halting fiscal drains through inefficient non-financial public corporations (NFPCs) are important ways to create fiscal space, particularly in the area of infrastructure. This paper reviews the financial performance of the NFPC sector in Bangladesh, with a specific focus on two major loss-making firms: Bangladesh Petroleum Corporation (BPC) and Power Development Board (PDB). The objective of this paper is to update the Bank’s knowledge on the financial performance of the NFPC sector and estimate the fiscal costs emanating from the sector.